PENGARUH STRATEGI PROMOSI DAN HARGA JUAL TERHADAP NILAI PENJUALAN PADA PT TRANS COFFEE BEAN KOTA MAKASSAR - Ali Baba (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to determine and analyze the effect of product quality, price and location to. A suitable sample was used by 50 respondents who met the criteria of this study. The sampling technique used is purposive sampling is the technique of determining the sample with certain considerations that have been determined first by the researchers. Statistical analysis methods consist of multiple linear regression analysis, simultaneous significant test (F test), significant partial test (t test), and determination analysis (R2). The results of this study indicate that the promotion strategy and selling price effect on the development of sales value in PT.Trans Coffee Bean Makassar. We recommend PT. Transcoffee Bean Makassar should always try to improve its products and services and provide information and promotions that hit the hearts of consumers in order to win the competition with other coffee shop and increase the attention of customers to buy drinks at Coffee Bean and offer products with utility and competitive prices and able to keep loyal customers with maximum service in order to remain secure and comfortable so that they are not affected by the services offered with competitors.